2019
DOI: 10.1111/jwip.12125
|View full text |Cite
|
Sign up to set email alerts
|

Māori knowledge under the microscope: Appropriation and patenting of mātauranga Māori and related resources

Abstract: Since the early 1990s there has been considerable global discussion and debate surrounding biodiscovery activities and the utilisation of both genetic resources (including biochemical derivatives) and associated traditional/Indigenous knowledge (TK/IK). Concerns about misappropriations and biopiracy have often been raised; however it has been difficult to quantify the scale of this problem beyond some common examples and anecdotes. This paper contributes to emerging research in this area (e.g., see Oldham et a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Important consideration must be given to access to and benefits of, Māori data. Here, the creation of access and benefit sharing (ABS) arrangements is a useful research tool (Lai et al, 2019).…”
Section: Tikanga Informs Researcher's Axiologymentioning
confidence: 99%
“…Important consideration must be given to access to and benefits of, Māori data. Here, the creation of access and benefit sharing (ABS) arrangements is a useful research tool (Lai et al, 2019).…”
Section: Tikanga Informs Researcher's Axiologymentioning
confidence: 99%
“…In the context of Aotearoa New Zealand, legal scholar Jessica Lai, along with Daniel Robinson and other collaborators, undertook a patent landscape that focussed on the protection of plants with which mātauranga Māori is known to be associated. 83 Their analysis centred on plant species that have been customarily used by iwi, hapū, and whānau Māori, as identified in publications on rongoā (Māori medicine). 84 Research revealed nearly 2000 patent families covering 41 plant species, with the majority of claims related to a handful of endemic or nearendemic species such as red mānuka (Leptospermum scoparium), harakeke (New Zealand flax; Phormium tenax), kokihi (New Zealand spinach; Tetragonia tetragonioides), kānuka (Kunzea ericoides), and others.…”
Section: A Landscape Of Intellectual Property Rights For Taonga Plantsmentioning
confidence: 99%
“…A limited number of attempts exist to quantify and identify “biopiracy”, use of Indigenous knowledge, and related spurious patents in the patent system (for example see Lai et al 2019; Robinson 2010; Robinson and Raven 2017). Broad scale patent landscaping or patent mapping has been used by Oldham et al (2013) to determine the scale of the use of biological diversity—using species names—globally.…”
Section: Emu As Oilmentioning
confidence: 99%
“…This paper, along with others (Lai et al 2019; Robinson and Raven 2017) seeks to narrow Oldham et al’s global metrics approach to species that may have traditional and Indigenous knowledge associated with them. The research for this paper is based on a simple search of “emu oil” in the Lens (https://www.lens.org/), in the title, abstract and claims sections, and the full text of patents for broader results.…”
Section: Emu As Oilmentioning
confidence: 99%